Asymmetric Organocatalysis Accelerated via Self‐Assembled Minimal Structures. Issue 39 (14th September 2021) - Sinibaldi, Arianna; Della Penna, Francesca; Ponzetti, Marco; Fini, Francesco; Marchesan, Silvia; Baschieri, Andrea; Pesciaioli, Fabio; Carlone, Armando
Abstract: Self‐assembling minimalistic peptides embedded with an organocatalytic moiety were designed. By controlling the formation of fibrils via external intervention, it was shown that the activation is accelerated when the organocatalyst is in its supramolecular state. The effect of the accelerated catalysis was demonstrated in a Michael benchmark reaction. Abstract : Self‐assembling minimalistic peptides embedded with an organocatalytic moiety were designed and tested in a Michael reaction as a proof of concept for accelerated organocatalysis.